1990
DOI: 10.1039/c39900000144
|View full text |Cite
|
Sign up to set email alerts
|

Generation of FeIIIOEP-hydrogen peroxide complex (OEP = octaethylporphyrinato) by reduction of FeIIOEP–O2with ascorbic acid sodium salt

Abstract: ESR and optical absorption spectra have been recorded for a frozen dimethylformamide (DMF) solution of the complex FelllOEP( -OH)( -0OH) (OEP = octaethylporphyrinato) prepared by mixing Fel1OEP(pyridine)-O2 with ascorbic acid sodium salt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 4 publications
0
30
0
Order By: Relevance
“…9 It also exhibited an EPR spectrum (77 K) indicative of a low-spin ferric complex with anomalously small g anisotropy. The peroxide complexes Fe 3+ -OEP(OOH) 212 and Fe 3+ "TMP(OOH) 213 were also reported. The EPR spectra of these peroxide complexes contrasted with those of the high-spin ferric peroxo porphyrin complexes discussed earlier and were consistent with those of Fe m (hemoglobin)(OOH) and Fe'"(horseradish peroxidase)(OOH).…”
Section: Heme and Pseudo-heme Iron Dioxygen Complexesmentioning
confidence: 93%
“…9 It also exhibited an EPR spectrum (77 K) indicative of a low-spin ferric complex with anomalously small g anisotropy. The peroxide complexes Fe 3+ -OEP(OOH) 212 and Fe 3+ "TMP(OOH) 213 were also reported. The EPR spectra of these peroxide complexes contrasted with those of the high-spin ferric peroxo porphyrin complexes discussed earlier and were consistent with those of Fe m (hemoglobin)(OOH) and Fe'"(horseradish peroxidase)(OOH).…”
Section: Heme and Pseudo-heme Iron Dioxygen Complexesmentioning
confidence: 93%
“…These studies were able to show that the observed species were five-coordinate and high-spin on the basis of their electronic absorption, EPR, and 1 H NMR spectra [50][51][52]. Compounds 18a-19 ( Figure 8) were the first six-coordinate examples [53][54][55] and differed from their five-coordinate counterparts insofar as they displayed EPR spectra characterized by a low g dispersion, consistent with a low-spin Fe(III) center and similar to spectra reported for hydroperoxo (alkylperoxo) adducts of hemoglobin, horseradish peroxidase, and bleomycin [56][57][58].…”
Section: Fe(iii)-hydroperoxo (Alkylperoxo) Intermediatesmentioning
confidence: 97%
“…These reactions are often performed under basic conditions to generate ROO À to yield either a fiveor six-coordinate product. It has also been demonstrated that reduction of an Fe(II)-superoxide followed by protonation can yield a hydroperoxide intermediate, although these examples are rare [23,54].…”
Section: Fe(iii)-hydroperoxo (Alkylperoxo) Intermediatesmentioning
confidence: 97%
“…In the catalytic oxidation cycle of cytochrome P450, one of the essential steps is protonation of an Fe(III) dianion complex to give an Fe-OOH complex and cleavage of the O-O bond to give a reactive ironoxo species [6]. However, investigation of these M-OOH porphyrins have been limited, due to instability of the species, although unstable iron porphyrins bearing an OOH group have been investigated at very low temperatures [24,25].…”
Section: Introductionmentioning
confidence: 99%